Implementasi Pendidikan Akidah Akhlak dalam Meningkatkan Nilai-nilai Karakter Pada Peserta Didik - Agus Maryono (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2021)
The research thesis is qualitative. The nature of the research is descriptive, while the data collection tool consists of observation, interview and documentation, and analysis techniques have three components: data reduction, data presentation and conclusion. The result of data analysis that the Implementation of Akidah Akhlak Education in Increasing the Values of Character in Students in MA ASSALAM Subdistrict of Bangilan of Tuban Regency by way of emotional approach, positive behaviour building approach with the repetitive, deductive and inductive dogmatic method and strategies and techniques of school arrangement and conducive classrooms, religious guidance for teachers, procurement of religious extracurricular activities in schools, Steps to realize moral education in improving the character values of the participants in MA ASSALAM understands the problems of participants educate students in the school environment and community environment, understand the causes and provide solutions. Supporting infrastructure facilities for the education of Akidah Akhlak in improving the values of the characters in Educational Participants in MA ASSALAM are: (1) There is a debriefing for teachers as educators. (2) The mutual commitment is clearly defined, (3) There is a special orientation, (4) There is a follow-up as a step to create change and affirmations-up as a step to create change and affirmation.